A Multi-Strategy Method for Spot Center Localization and Error Measurement in Engineering Applications - Peng, Xiaofeng; Liao, Min (International Journal of Advanced AI Applications, 2026)
To address the challenges of existing automatic spot-center positioning methods in engineering applications, namely the difficulty in simultaneously achieving real-time performance, positioning accuracy, and detection stability, this study proposes a multi-strategy approach for spot-center positioning and error measurement. This method integrates the center of mass approach, elliptical fitting, and two-dimensional Gaussian fitting. It selects strategies based on real-time and accuracy constraints for different detection scenarios, while introducing a unified error measurement model for the quantitative evaluation of positioning results. By establishing a pixel-to-physical coordinate mapping, a systematic evaluation of spot center localization and aiming error was achieved using metrics such as the root mean square error. Experiments demonstrated that under both static and dynamic conditions, this method exhibits excellent robustness and stability, meeting the comprehensive requirements for accuracy and real-time performance in engineering applications.